Examining the use of theories in construction management research: 2005 to 2014 / Ayokunle Olubunmi Olanipekun and Bo Paul Xia - Olanipekun, Ayokunle Olubunmi; Bo, Paul Xia (Faculty of Architecture, Planning and Surveying, 2017)
The use of theories in construction management research (CMR) is very important so as to generate an acceptable and generalizable construction management (CM) knowledge. This has generated a lot of research contributions that revealed the need to examine the use of theories and models in CMR by answering the following questions: (1) how often theories and models have been used in CMR?, (2) what are the types of, and the base disciplines of theories and models used in CMR? and, (3) what methodological patterns were followed by the theories and models used in CMR? In answering these questions, 846 empirical research articles published in Construction Management and Economics (CME) from 2005-2014 were quantitatively analysed using descriptive statistics such as frequency and percentage analysis, and statistical hypothesis tests such as chi-square and t-test. The 10-year period between 2005 and 2014 was demarcated into a 2 five-year periods (2005-2009 and 2010-2014), so as to ensure a clearer grasp of the trend of events over the period. The findings suggest that CMR continues to be generally a theoretical. The conclusion was made based on the findings, while the use of theories in future CMR was recommended.